La regulación de los contratos internacionales en la Unión Europea - López-Tarruella Martínez, Aurelio (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
The aim of this paper is to provide a general overview of the rules of Private international law inthe European Union that deal with international contracts. The first part of the paper focuses on the analysis of the rules of Regulation 1215/2012 (Brussels I) that determine the international jurisdiction of the courts of the Member States to hear about contractual disputes. For this purpose a distinction is made between situations in which the parties have made use of forum-choice clauses and situations in which this has not been the case. The second part analyses Regulation 593/2008 (Rome I) on the law applicable to contractual obligations. As in the previous section, a distinction is made on whether the parties have agreed on the applicable law or not. This part also includes an analysis of the mechanisms in the Regulation allowing Member States to saveguardtheir national or EU interests.

El presente trabajo tiene por objeto ofrecer una aproximación general de las normas de derechointernacional privado de la Unión Europea que regulan los contratos internacionales. En la primera parte, se abordan las normas del Reglamento 1215/2012 (Bruselas I) por las que se determinan los tribunales competentes para conocer de demandas en estas materias. Para ello se establece una distinción según las partes del contrato hayan hecho uso de una cláusula de sumisión o no. En la segunda parte, se analiza el Reglamento 593/2008 (Roma I) sobre la ley aplicable a las obligaciones contractuales. De nuevo, en esta sección del trabajo se distingue según las partes hayan elegido o no la ley aplicable al contrato. También se analizan los mecanismos que establece el Reglamento para garantizar la salvaguarda de los intereses fundamentales del foro en materia patrimonial.
The Regulation of International Contracts in the European Union
Keywords: International Contracts; European Union; International Jurisdiction; Applicable Law; Contratos Internacionales; Unión Europea; Competencia Judicial Internacional; Ley Aplicable; https://purl.org/pe-repo/ocde/ford#5.09.01